Multi-dimensional research impact assessment through bibliometrics, altmetrics, semantometrics, and webometrics - Marouf, Ahmed Al; Turin, Tanvir C (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Research impact assessment (RIA) has emerged as a critical approach for evaluating the societal, academic, and policy-related influence of scholarly work, particularly within the evolving landscape of Open Science. This paper provides a synthesis of quantitative RIA metrics, which offer standardised, data-driven insights into the reach and significance of research outputs. It outlines four principal methodologies: (i) bibliometrics (analyse citation patterns through indicators such as citation counts, co-citation, and bibliographic coupling); (ii) altmetrics (track online engagement and dissemination); (iii) semantometrics (assess textual contributions using semantic similarity measures); and (iv) webometrics (evaluate digital presence through web interactions and backlink analysis). While these quantitative approaches are valuable for benchmarking and strategic decision-making, they often fail to capture the nuanced societal and intellectual impacts of research. To address this limitation, the paper advocates for a hybrid assessment model that integrates quantitative metrics with qualitative methods, such as case studies and narrative analyses, to provide both scalability and contextual depth. Ultimately, the work underscores the importance of critically and judiciously interpreting RIA metrics to fully reflect the multifaceted nature of research impact across disciplines and stakeholder domains.